Semantic question answering of umrah pilgrims to enable self-guided education - Mohd Sharef, Nurfadhlina; Murad, Masrah Azrifah; Mustapha, Aida; Shishechi, Saman (IEEE (IEEE Xplore), 2013)
Umrah as a pilgrimage to Mecca is obligatory in Islam madhab. Pilgrims can gain their knowledge about the requirements of Umrah using books, expert and existent question answering systems but still they suffer from the lack of complexity and natural language patterns. This paper proposes the semantic based question answering system to able pilgrims to compose any question about Umrah in natural language format. The proposed system used ontology to represent the knowledge about ritual of Umrah and Pilgrims. The question complexity for question in natural language is observed since it needs to be map with the contents in the ontology. An Umrah Knowledge module in this system covers all the rules and fact in the ontology format and the Educational modules is responsible for question answering interaction.